Perspectives on diacylglycerol-induced improvement of insulin sensitivity in type 2 diabetes - Daoming Li; Yang Zhu; Yonghua Wang; Qiong Zou; Jinzhu Duan; Dongxiao Sun-Waterhouse; Baoguo Sun (Food Science and Human Wellness)
Diacylglycerol (DAG)-based edible oils have attracted increasing research interest owing to their health-promoting properties. Recent animal and human studies showed that an increased 1,2-DAG content in the liver and skeletal muscle may cause insulin resistance. However, earlier studies using animal models or humans reported that dietary DAGs with a 1,2-DAGs to 1,3-DAGs ratio of approximately 3:7 could improve insulin sensitivity in type 2 diabetic patients. This conflict raises the question of whether there is a link between the ingested DAGs and endogenous DAGs during their metabolism. To make a contribution to this field, this review provides an overview of the metabolic pathways of ingested DAGs and biological roles of DAGs (ingested and endogenous) in the change of insulin sensitivity. Accordingly, strategies for further investigations on the metabolism of DAGs are proposed.